(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Various professional groups of the able-bodied population, such as medical workers, railway transport workers, teachers, and artists, quite often suffer from occupational diseases. Musicians, actors, and artists striving for mastery are forced to be at the limit of their physical, emotional, and intellectual capabilities. Railway transport workers (conductors, locomotive drivers) and teachers constantly experience violations in work and rest and are under psycho-emotional stress. As for the professional activity of medical worker, railway transport workers (conductors, locomotive drivers) and teachers, regardless of the type of work performed, it belongs to a group of professions with increased moral responsibility for the health and life of individuals, groups of the population and society as a whole. Art therapy may become a possible method of preventing occupational diseases in this group of patients.